11C-Pittsburgh B PET Imaging in Cardiac Amyloidosis - Lee, Seung-Pyo; Lee, Eun Seong; Choi, Hongyoon; Im, Hyung-Jun; Koh, Youngil; Lee, Min-Ho; Kwon, Ji-Hyun; Paeng, Jin Chul; Kim, Hyung-Kwan; Cheon, Gi Jeong; Kim, Yong-Jin; Kim, Inho; et al. (JACC. Cardiovascular imaging, 2015)
This study sought to investigate the efficacy of 11C-Pittsburgh B (PiB) positron emission tomography (PET)/computed tomography (CT) in the diagnosis of cardiac amyloidosis. The PiB compound has been promising for detection of amyloid deposits in the brain. A total of 22 consecutive patients were enrolled in this prospective pilot study of monoclonal gammopathy patients with suspected cardiac amyloidosis. The study consisted of a series of 11C-PiB PET/CT, echocardiography, cardiac magnetic resonance, and endomyocardial biopsy within a 1-month period. In addition, 10 normal subjects were recruited to determine the most optimal cut-off value for a positive 11C-PiB PET/CT scan. Among the 22 patients, 15 patients were diagnosed as cardiac amyloidosis by endomyocardial biopsy and 5 patients had undergone chemotherapy previously before the 11C-PiB PET/CT. There were no differences in echocardiographic parameters between patients with versus without cardiac amyloidosis, except for a marginal difference in the left ventricular end-diastolic dimension (median 41.0 mm [range 33.0 to 49.0 mm] vs. 50.0 mm [range 38.0 to 55.0 mm], p = 0.066). 11C-PiB PET/CT was positive in 13 of 15 biopsy-proven cardiac amyloidosis patients, whereas none of the patients without cardiac amyloidosis demonstrated positive 11C-PiB PET/CT scan results. The maximal myocardium-to-blood cavity ratio was significantly different between patients with versus without cardiac amyloidosis (median 3.9 [range 1.7 to 19.9] vs. 1.0 [range 0.8 to 1.2], p < 0.001). In association with the significant difference of 11C-PiB uptake in the myocardium between the chemotherapy naïve versus the previous chemotherapy group (median 10.4 [range 1.7 to 19.9] vs. 2.3 [range 1.7 to 3.8], p = 0.014), all except 1 patient among the 5 previously treated patients had responded to chemotherapy by serum free light chain assay results at the time of 11C-PiB PET/CT scan. 11C-PiB PET/CT may be valuable for the diagnosis of cardiac amyloidosis noninvasively. Whether 11C-PiB PET/CT may be a good surrogate marker of active light chain deposition in the myocardium warrants further investigation in a larger number of patients.